2014
DOI: 10.1016/j.nicl.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

GABA and glutamate in schizophrenia: A 7 T 1H-MRS study

Abstract: Schizophrenia is characterized by loss of brain volume, which may represent an ongoing pathophysiological process. This loss of brain volume may be explained by reduced neuropil rather than neuronal loss, suggesting abnormal synaptic plasticity and cortical microcircuitry. A possible mechanism is hypofunction of the NMDA-type of glutamate receptor, which reduces the excitation of inhibitory GABAergic interneurons, resulting in a disinhibition of glutamatergic pyramidal neurons. Disinhibition of pyramidal cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
109
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 69 publications
(102 reference statements)
15
109
4
3
Order By: Relevance
“…This ratio finding might be determined by the trend for creatine/water to be higher especially in untreated patients than in healthy controls (for effect sizes, see Table S6 in the data supplement). These data are generally consistent with several studies of GABA levels in the prefrontal cortex (10,11,15,17), in the occipital cortex (13,14,17), and in the hippocampal formation (12), which found GABA levels to be reduced or unchanged in patients with schizophrenia compared with healthy controls. However, our findings differ in directionality from those by Ongür et al (20) in the dorsal anterior cingulate and Kegeles et al (19) in the medial prefrontal cortex (see the Supplementary Discussion section in the data supplement).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This ratio finding might be determined by the trend for creatine/water to be higher especially in untreated patients than in healthy controls (for effect sizes, see Table S6 in the data supplement). These data are generally consistent with several studies of GABA levels in the prefrontal cortex (10,11,15,17), in the occipital cortex (13,14,17), and in the hippocampal formation (12), which found GABA levels to be reduced or unchanged in patients with schizophrenia compared with healthy controls. However, our findings differ in directionality from those by Ongür et al (20) in the dorsal anterior cingulate and Kegeles et al (19) in the medial prefrontal cortex (see the Supplementary Discussion section in the data supplement).…”
Section: Discussionsupporting
confidence: 91%
“…While some studies (10)(11)(12) found no differences in patients with schizophrenia compared with healthy controls, others found reduced levels in the occipital (13,14) and prefrontal (15) cortices (including the dorsal anterior cingulate cortex in patients over 35 years of age [16]) and in the basal ganglia (17). In contrast, our preliminary data in a small group of patients who do not overlap with the ones presented here (18) showed elevated GABA levels in the dorsal anterior cingulate in treated patients with psychosis compared with healthy controls.…”
Section: Objectivementioning
confidence: 96%
“…Consistent with this possibility, pharmacological models of SCZ often propose a distributed disruption in E/I across cortical circuits. This finding is supported by clinical magnetic resonance spectroscopy studies showing GABA and glutamate deficits across the cortex in SCZ (7,(82)(83)(84).…”
Section: Focal Vs Global Neuropathology Producing Preferential Assocsupporting
confidence: 56%
“…GABA alterations in schizophrenia are also controversial [15, 21, 27, 28, 3639]. Several studies have reported lower GABA levels in the ACC, bilateral calcarine sulci, and mPFC in chronic schizophrenia [15, 38, 39]. However, unchanged or elevated GABA levels in the ACC and mPFC have also been observed [15, 28, 37, 39].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported lower GABA levels in the ACC, bilateral calcarine sulci, and mPFC in chronic schizophrenia [15, 38, 39]. However, unchanged or elevated GABA levels in the ACC and mPFC have also been observed [15, 28, 37, 39]. Evidence of GABA alterations in first-episode schizophrenia remains limited [22].…”
Section: Introductionmentioning
confidence: 99%